2016
DOI: 10.1016/j.jmii.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Role of aerosolized colistin methanesulfonate therapy for extensively-drug-resistant Acinetobacter baumannii complex pneumonia and airway colonization

Abstract: Aerosolized CMS therapy has acceptable efficacy for XDRAB pneumonia, but no proven efficacy for XDRAB airway colonization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…However, these data have not been confirmed in other studies [104,170]. A recent retrospective study showed an acceptable efficacy of nebulized colistin in patients with extremely resistant A. baumanii pneumonia but was not effective in patients with respiratory tract colonization [171].…”
Section: Should Inhaled Antibiotics Be Prescribed To Donors or Recipimentioning
confidence: 82%
“…However, these data have not been confirmed in other studies [104,170]. A recent retrospective study showed an acceptable efficacy of nebulized colistin in patients with extremely resistant A. baumanii pneumonia but was not effective in patients with respiratory tract colonization [171].…”
Section: Should Inhaled Antibiotics Be Prescribed To Donors or Recipimentioning
confidence: 82%
“…In our population of patients with KPC-Kp septic shock, a carbapenem was the most used antibiotic, mainly in combination with colistin, tigecycline, and/or gentamicin. On the other hand, a carbapenem was used in combination with colistin and/or rifampin for the treatment of MDR-AB infections (27)(28)(29). Despite the observation of only 1 patient with MDR-AB infection due to a colistinresistant strain, a very low proportion of patients were treated with 2 or more antibiotics showing in vitro activity against the isolates of MDR-AB; this probably explains the very high mortality rates observed in this population.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] XDR-Acb pneumonia was defined as new infiltrates or consolidation on radiographic evidence, as well as the consistent sputum Gram stain finding (> 25 leukocytes/low power field [LPF], < 10 epithelial cells/LPF, and numerous gram-negative pleomorphic coccobacilli seen by high power field of smear) and culture of tracheal aspirate growing heavy XDR-Acb complex (the microbiological definition is seen as follows). [ 4 , 12 ] Using the propensity matching score, we selected the control group patients who received AS-CMS alone based on age (± 5 years) and Acute Physiology and Chronic Health Evaluation (APACHE) II score (± 4 points) by the computers. An AS-CMS dose of 2 million international units thrice per day was used, and a TGC loading dose of 100 mg and 50 mg every 12 hours was administered.…”
Section: Methodsmentioning
confidence: 99%
“…[ 7 ] However, the colistin concentration in lung tissue is low when it is administered intravenously in mice and humans. [ 8 , 9 ] Aerosolized CMS (AS-CMS) was prescribed as either an adjuvant drug [ 10 12 ] or monotherapy [ 13 ] for XDR-Acb pneumonia with clinically variable successful rates. Nevertheless, a survey on the use of CMS in treating patients with microbiologically documented ventilator-associated pneumonia (VAP) addressed that AS-CMS therapy was the only independent predictor of clinical cure in patients with VAP.…”
Section: Introductionmentioning
confidence: 99%